Nature-Based Solutions for Urban Renewal in Post-Industrial Cities (Routledge, 2025)
This book, based on the experiences and insights gained during the Horizon 2020 project proGIreg, offers a detailed overview of targeted nature-based solutions and their impacts on various key sustainability areas, guiding readers through the spatial analysis, co-design, and implementation processes of cities in Europe and Asia. Chapters shed light on the challenges and opportunities encountered in each location, including Germany, Italy, Croatia, Bosnia and Herzegovina, Greece, Portugal, Romania and China. It also shares essential lessons learned and a wide range of indicators crucial for assessing the benefits of nature-based solutions on social innovation, circular economy, biodiversity, and health. Finally, the focus of this book shifts to the future of nature-based solutions as catalysts for new and green community economies as well as policies aimed at addressing climate change and urban renewal. The lessons and insights from the projects highlighted in this book will be valuable for urban planners and policymakers worldwide, as well as for a broader audience interested in nature-based solutions and urban regeneration. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons CC-BY 4.0 license.